A Foresight Study of Artificial Intelligence Application through Voice Recognition in Detecting and Assisting Emotional Distress of Secondary Student in Malaysia - Rodzalan, Shazaitul Azreen; Ibrahim, Irdeena Solehah (Research in Management of Technology and Business, 2021)
Stress and depression have a negative impact on learning process and academic performance of secondary students. Thus, this study aims to examine issues and drivers related to their emotional distress as school environment cause some of the behavioral problems. Each student face challenges and conflicts when changes occur within them either in terms of biological, physical, emotional and mental. In coping with their emotional distress, one way is through sharing their feelings and thoughts via voice recognition application using Artificial Intelligence (AI) technology. The application can assist them by talking to them, and the student does not have to worry about the others because the machine does not have feelings such as judgmental or biased. The objectives of this study are first, to examine issues and drivers on AI application via voice-recognition in detecting and assisting emotional distress among secondary students and second, to foresight future scenario related to AI application via voice recognition. This study used STEEPV analysis in examining the issues and drivers related to AI application. A total of 280 secondary students in Johor Bahru completed the survey. The results of the survey concluded that are technology development enables the detecting of emotional distress through voice recognition and secondly, the needs in automatically detection of the sign and early symptoms for students and four scenarios on the future trends that were discovered from scenario building. This research will give benefits to students and counsellor teachers as voice recognition able to detect and assisting emotional distress, therefore early precaution can be taken by stakeholders.